Autoimmune related pancreatitis. (1st July 2002) - Okazaki, K; Chiba, T
Abstract : Since the first documented case of a particular form of pancreatitis with hypergammaglobulinaemia, similar cases have been reported, leading to the concept of an autoimmune related pancreatitis or so-called "autoimmune pancreatitis". Although it has not yet been widely accepted as a new clinical entity, the present article discusses the recent concept of autoimmune pancreatitis.